"One-Two Punch": Synergistic ß-Lactam Combinations for Mycobacterium abscessus and Target Redundancy in the Inhibition of Peptidoglycan Synthesis Enzymes. (11th June 2021) - Nguyen, David C; Dousa, Khalid M; Kurz, Sebastian G; Brown, Sheldon T; Drusano, George; Holland, Steven M; Kreiswirth, Barry N; Boom, W Henry; Daley, Charles L; Bonomo, Robert A
Abstract: Mycobacterium abscessus subsp. abscessus is one of the most difficult pathogens to treat and its incidence in disease is increasing. Dual β-lactam combinations act synergistically in vitro but are not widely employed in practice. A recent study shows that a combination of imipenem and ceftaroline significantly lowers the minimum inhibitory concentration of clinical isolates, despite both drugs targeting the same peptidoglycan synthesis enzymes. The underlying mechanism of this effect provides a basis for further investigations of dual β-lactam combinations in the treatment of M. abscessus subsp. abscessus, eventually leading to a clinical trial. Furthermore, dual β-lactam strategies may be explored for other difficult mycobacterial infections. Abstract : Interest in dual β-lactam treatment for Mycobacterium abscessus subsp. abscessus is growing. We summarize recent work that suggests drug target redundancy underlies in vitro efficacy and outline the implications this has for future studies for this difficult infection.